An Interrogation of Perspectives on Pre-Mosaic Narratives Tithe-Related Narratives - Fawenu, Bamidele Olusegun (KWASU Journal of Religious Studies, 2018)
Tithing which describes the giving of ten per cent of one's income for religious purposes is a popular religious practice among Christians. Its occurrences and practice in the Old Testament can be classified into three eras; pre-mosaic, mosaic and post-mosaic. Opinions are divided on Christian adoption of this ancient Israelite practice. The pro-tithing perspective leans strongly on Abram's model to argue that contrary to the anti-tithing dubbing of the practice as legalism, the practice predated the Mosaic Law. Therefore, this paper examines the three references (Genesis 4:1-10; Genesis 14:8-24 and Genesis 28:10-22) to tithing prior to the Mosaic age and interrogates the dual perspectives arising from them with the intent to ascertain the tenability of the claim of tithing advocates. Historical and analytical methods were used in achieving the set goal of this paper. Data from the biblical passages as well as from scholars' views were critically appraised. It was discovered that the divergent opinions on tithing arc due to making of assertions and querying of the narratives beyond what they were scripted to supply. Therefore, while the heroism of the biblical patriarchs of faith can be emulated, on the strength of God's ownership of man and the inestimable blessing of redemption that believers in Christ enjoy, serving God with material possession should not be conditional neither should it be by compulsion.